NEW SPECIES OF ASTEROCHERES AND FIRST RECORD FOR CUBA OF A. CRINOIDICOLA (COPEPODA: SIPHONOSTOMATOIDA: ASTEROCHERIDAE) - Varela, Carlos (2010)
Two species of copepods belonging to the genus Asterocheres were found in recent collections in the North of Matanzas province. The one associated to the sponge of the genus Callyspongia Duchassaing y Michelotti, 1864 is described as a new species of siphonostomatoid copepod to science. The differences among the new specie and the more similar ones are also presented. A. crinoidicola, associated to a crinoid of the genus Davidaster Hoggett y Rowe, 1986 is recorded for the first time for the Cuban Archipelago.